2011
DOI: 10.1186/1471-2458-11-330
|View full text |Cite
|
Sign up to set email alerts
|

The influence of both individual and area based socioeconomic status on temporal trends in Caesarean sections in Scotland 1980-2000

Abstract: BackgroundCaesarean section rates have risen over the last 20 years. Elective Caesarean section rates have been shown to be linked to area deprivation in England, women in the most deprived areas were less likely to have an elective section than those in the most affluent areas. We examine whether individual social class, area deprivation or both are related to Caesarean sections in Scotland and investigate changes over time.MethodsRoutine maternity discharge data from live singleton births in Scottish hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 29 publications
4
38
3
1
Order By: Relevance
“…The findings support previous research showing an association between pregnancy and social factors and rates of CS [9][10][11][12]18,19]. We found that the father's occupation was associated with CS -families with fathers in unskilled occupations were less likely to undergo CS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings support previous research showing an association between pregnancy and social factors and rates of CS [9][10][11][12]18,19]. We found that the father's occupation was associated with CS -families with fathers in unskilled occupations were less likely to undergo CS.…”
Section: Discussionsupporting
confidence: 91%
“…The strongest of these include increased maternal age, particularly at the time of first birth [9][10][11][12], as well as the mother being overweight or obese [8,13]. In addition, once CS has been performed, the most likely mode of delivery in subsequent pregnancy is CS [14][15][16][17] Higher socio-economic status and possession of private health insurance are also associated with higher rates of CS [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…One of the unclear issues is the impact of childbirth on the development of postpartum incontinence in IBD patients; there is a need to investigate the effects of vaginal delivery on sphincter function, as well as on the development of perianal complications in patients with pre-existing perianal disease adjuvant to Crohn's and in patients with ulcerative colitis. In the last 20 years, statistics show an increase in the prevalence of Caesarean section births (19,(25)(26)(27). Prior studies have demonstrated a higher incidence of Caesarean section births in IBD patients compared to the general population (28,29); this is also seen in our results, where the number of CS births was signifi cantly higher in IBD patients compared to healthy controls.…”
Section: Discussionsupporting
confidence: 85%
“…This feature demonstrates the utility of the deprivation index as it can be used in situations where the individual-level variables of socioeconomic position are not available or are poorly recorded for certain subgroups (e.g., occupational social class of elderly people who have not worked for a number of years) 9 . Area deprivation measures are also used when individual-level measures are available; individual socioeconomic position and area deprivation can both have an effect on outcomes, independent of each other 15 . Area-based deprivation indicators can be linked to routinely collected administrative data, such as mortality and hospitalizations, where there is typically no information about the socioeconomic position of the individual.…”
Section: Introductionmentioning
confidence: 99%